Teaching Parallel and Distributed Computing Using a Cluster Computing Portal - Hong Lin (2013 IEEE International Symposium on Parallel & Distributed Processing, Workshops and Phd Forum, 2013)
This paper presents the establishment of cluster computing lab at a minority serving institution that aims to provide computing resources to support undergraduate computer science curriculum. We present a case study of using this platform to teach parallel and distributed computing topics in the operating system course. The evaluation of the teaching effectiveness is presented thereafter.